Creation of a database linking contextual small-area characteristics to successful aging: Contributions from GIS science - Corluka, Adrijana (University of Ottawa (Canada), 2004)
While medical geography has long contributed to epidemiological studies, applications of GIS in health research are now only beginning to be realized. Individual-level variables such as genetics or lifestyle do not fully explain the phenomena of health and disease---social and physical environments play a role in determining the health of populations as well. Using individual-level data from a cohort of close to 5000 elderly Canadians, GIS was used to create a spatial database of neighborhood socio-demographic and economic characteristics, based on proximity and containment analysis, to aid in understanding how environmental context influences successful aging in Canada. The work done for this thesis resulted in the creation of the first national combined spatial and aspatial database composed of demographic, socio-economic and GIS-derived local contextual spatial data linked to individual successful aging outcome data via postal code.
Keywords: Health Sciences, Public Health.